Biomedical Ti–Nb–O alloy with high strength and ultra-low Young’s modulus - Yue Gao; Jing Chen; Yiliang Gan; Xiongwei Liang; Heng Chen; Da Zeng; Changyi Yang; Wentao Jiang; Chaoli Ma; Wenlong Xiao (Materials Research Letters, 2025)
In this study, a novel (α+β) dual-phase Ti–19Nb–0.6O was developed and processed via additive manufacturing, featuring ultra-low Young’s modulus of 42 GPa approximating that of human bone, coupled with high strength (919 MPa), and 15% elongation. By utilizing post-heat treatment to adjust the distribution and content of the precipitated α phase, the elemental distribution of Nb and O between α and β phase was effectively manipulated, meanwhile, the β matrix stability was regulated, enabling the attainment of lower modulus and higher strength. These findings advance the development of biomedical titanium alloys produced using additive manufacturing, characterized by excellent mechanical performance.